A bulk alumina ceramic piece and method of making the same
Patent Information
- Application Number
- CN202611223482.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-30
AI Technical Summary
然而,氧化铝陶瓷的缺陷密度、致密性和晶体结构稳定性对其中子反射能力具有显著影响,当其内部存在气孔、裂纹等缺陷或密度分布不均时,会增大散射干扰并降低中子反射性能
[0003]本发明的目的在于提供一种大体积氧化铝陶瓷件的制造方法,提高氧化铝陶瓷件的成品质量。本发明还提供一种大体积氧化铝陶瓷件。
Smart Images

Figure CN123003267A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic materials, specifically relating to a large-volume alumina ceramic part and its manufacturing method. Background Technology
[0002] Alumina ceramics are widely used in cutting-edge fields such as aerospace and nuclear engineering due to their excellent high-temperature resistance, corrosion resistance, wear resistance, good neutron reflection performance, and chemical stability. Currently, the neutron reflector layer of advanced heat pipe microreactors is mainly made of alumina ceramics. Its function is to reflect neutrons leaking from the reactor core active region back into the active region to improve neutron economy and reactivity. Simultaneously, it utilizes its good thermal conductivity to conduct core heat to maintain temperature stability and ensure safe reactor operation. Alumina ceramics have good chemical stability, resisting harsh environmental corrosion such as high-temperature radiation, and can maintain structural and performance stability over a long period, thereby extending the reactor's service life. However, the defect density, compactness, and crystal structure stability of alumina ceramics have a significant impact on its neutron reflection capability. When defects such as pores and cracks exist inside, or when the density distribution is uneven, scattering interference increases and neutron reflection performance decreases. Although conventional manufacturing processes for alumina structural components are relatively mature, numerous technical challenges remain in preparing ultra-thick, high-density, large-size, and highly stable alumina ceramics. During molding, uneven stress distribution during pressing can easily lead to deformation and cracking of the green body. During sintering, controlling the uniformity of sintering temperature is difficult, and large temperature differences between the inside and outside of the green body can easily cause deformation and cracking, severely affecting dimensional accuracy and shape integrity. Process defects result in inhomogeneous microstructures, potentially leading to pores, cracks, and other defects within the material. These factors result in insufficient performance consistency in large-volume alumina ceramic components, making it difficult to meet the stringent requirements of reflective layer materials in demanding service environments. Therefore, providing a manufacturing method for large-volume alumina ceramic components that reduces internal defects and improves overall uniformity has significant practical value. Summary of the Invention
[0003] The purpose of this invention is to provide a method for manufacturing large-volume alumina ceramic parts, thereby improving the quality of the finished alumina ceramic parts. This invention also provides a large-volume alumina ceramic part.
[0004] According to one embodiment of the present invention, a method for manufacturing a large-volume alumina ceramic part is provided, the method comprising the following steps: Step a): Provide alumina granular raw material; Step b): The alumina granular raw material is loaded into a mold for dry pressing. The dry pressing process involves sequentially applying pressure to the alumina granular raw material to a first pressure, a second pressure, and a third pressure, and holding the pressure at each pressure. Then, the pressure is released to atmospheric pressure to obtain a dry-pressed blank. The density of the dry-pressed blank is not less than 30%. Step c): The dry-pressed billet is subjected to cold isostatic pressing to obtain a cold isostatic pressed billet; the density of the cold isostatic pressed billet is not less than 50%. Step d): The cold isostatic pressed billet is heated to 500℃-700℃ and held for 5h-10h, then heated to 1100℃-1300℃ and held for 2h-5h to obtain the first sintered billet; Step e): Perform surface processing and drying on the first sintered blank; Step f): Heat the first sintered green body to 1100℃-1300℃ and hold for 5h-10h, then heat to 1500℃-1800℃ and hold for 2h-5h; after cooling, the finished alumina ceramic part is obtained.
[0005] This method employs a three-stage stepped pressure dry pressing process to progressively densify the powder, avoiding uneven stress distribution caused by a single high-pressure impact and reducing green body deformation and cracking. Cold isostatic pressing utilizes isotropic uniform pressure to eliminate residual density gradients from dry pressing, increasing the green body density to over 50%, providing a uniformly dense green body for subsequent sintering. The segmented heating and cooling paths of low-temperature and high-temperature sintering effectively control the temperature difference between the inside and outside of the green body, reducing the risk of thermal stress cracking and ensuring uniform sintering temperature and microstructure. The two-stage forming and two-stage sintering work together to effectively control stress and temperature gradients, thereby effectively improving problems such as deformation, cracking, uneven microstructure, and poor performance consistency in the manufacturing process of ultra-thick, large-size alumina ceramics, ultimately obtaining large-volume alumina ceramic parts with complete structure, uniform density, and high compactness.
[0006] Furthermore, in some embodiments, the alumina granular raw material has a particle size of 50μm-300μm and a flowability of 2s / 50g-4s / 50g.
[0007] Furthermore, in some embodiments, the alumina particle raw material is a hollow spherical particle, and the alumina particle raw material is manufactured using a spray granulation process.
[0008] Further, in some embodiments, in step b) when the maximum filling depth of the alumina granular raw material in the mold is less than 30 mm, the first pressure is 0.3 MPa-0.6 MPa, and the holding time is not less than 10 s; the second pressure is 8 MPa-12 MPa, and the holding time is not less than 30 s; the third pressure is 25 MPa-35 MPa, and the holding time is not less than 30 s; when the maximum filling depth of the alumina granular raw material in the mold is 30 mm-100 mm... When the first pressure is 1MPa-1.7MPa and the holding time is not less than 10s; the second pressure is 17MPa-23MPa and the holding time is not less than 40s; the third pressure is 35MPa-45MPa and the holding time is not less than 30s; when the maximum filling depth of the alumina particles in the mold is greater than 100mm, the first pressure is 0.5MPa-1.7MPa and the holding time is not less than 20s; the second pressure is 35MPa-45MPa and the holding time is not less than 30s; the third pressure is 90MPa-110MPa and the holding time is not less than 30s; the pressurization rate is 0.5MPa / s-2MPa / s.
[0009] Further, in some embodiments, in step b), after pressurizing to the third pressure and holding the pressure, when the maximum depth of alumina particle material filling in the mold is less than 30 mm, the pressure is released to atmospheric pressure at a rate of 0.8 MPa / s-1.2 MPa / s; when the maximum depth of alumina particle material filling in the mold is 30 mm-100 mm, the pressure is first released to 13 MPa-17 MPa at a rate of 0.4 MPa / s-0.6 MPa / s and held for at least 10 s, and then released to atmospheric pressure at a rate of 0.8 MPa / s-1.2 MPa / s; when the maximum depth of alumina particle material filling in the mold is greater than 100 mm, the pressure is first released to 50 MPa-70 MPa at a rate of 0.4 MPa / s-0.6 MPa / s and held for at least 30 s, and then released to atmospheric pressure at a rate of 0.8 MPa / s-1.2 MPa / s.
[0010] Further, in some embodiments, the specific process of the cold isostatic pressing in step c) is as follows: pressurize to 0.5MPa-1.7MPa and hold for 0-30s, then pressurize to 25MPa-35MPa at a rate of 0.8MPa / s-1.2MPa / s and hold for 0-90s, then pressurize to 70MPa-90MPa at a rate of 1.7MPa / s-2.3MPa / s and hold for 0-120s; then depressurize to 35MPa-45MPa at a rate of 0.4MPa / s-0.6MPa / s and hold for 0-60s, and finally depressurize to atmospheric pressure at a rate of 0.8MPa / s-1.2MPa / s.
[0011] Furthermore, in some embodiments, in step d), the heating time for heating the cold isostatic pressing billet to 500℃-700℃ is 24h-48h, and the heating time for heating to 1100℃-1300℃ is 20h-30h; during cooling, the billet is first cooled to 500℃-700℃ over a cooling time of 20h-30h, and then naturally cooled to room temperature.
[0012] Furthermore, in some embodiments, in step e), the drying temperature is 80℃-120℃ and the drying time is 12h-24h.
[0013] Furthermore, in some embodiments, in step f), the heating time to 1100℃-1300℃ is 10h-20h, and the heating time to 1500℃-1800℃ is 80h-120h; during cooling, the temperature is first lowered to 500℃-700℃ over a period of 120h-150h, and then naturally cooled to room temperature.
[0014] According to another aspect of the present invention, a large-volume alumina ceramic part is provided, which is manufactured using the manufacturing method of the large-volume alumina ceramic part provided in any of the foregoing embodiments.
[0015] Furthermore, in some embodiments, the density of the large-volume alumina ceramic part is not less than 95%. Attached Figure Description
[0016] Figure 1 A photograph of a dry-pressed billet in one embodiment; Figure 2 Photograph of the first sintered blank in another embodiment; Figure 3 A photograph of the finished alumina ceramic part in another embodiment; Figure 4 Here is a scanning electron microscope image of the finished alumina ceramic part in another embodiment; Figure 5 These are photographs of a pair of proportionally scaled dry-pressed billets.
[0017] The purpose of the above figures is to provide a detailed description of the invention so that those skilled in the art can understand the technical concept of the invention, and not to limit the invention. Detailed Implementation
[0018] The present invention will now be described in further detail with reference to specific embodiments and accompanying drawings.
[0019] The term "embodiment" as used herein means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment herein. The phrase appearing in various places in the specification does not necessarily refer to the same embodiment, nor is it limited to mutually exclusive, independent, or alternative embodiments. Those skilled in the art will understand that the embodiments herein can be combined with other embodiments without causing structural conflicts.
[0020] To reduce the risk of cracking, deformation, and uneven internal structure during the sintering and forming of large-volume alumina ceramic parts, and to improve the finished product quality of large-volume alumina ceramics, one embodiment of the present invention provides a method for manufacturing large-volume alumina ceramic parts, the method comprising the following steps: Step a): Provide alumina granular raw material, which is hollow spherical granules; in a preferred embodiment, the particle size is 50μm-300μm, the flowability is 2s / 50g-4s / 50g, and it is manufactured using a spray granulation process. Hollow spherical granules have good uniformity and flowability, which can reduce initial defects in the microstructure during pressing and sintering.
[0021] Step b): The alumina granular raw material is loaded into a mold for dry pressing to obtain a dry-pressed green body. Dry pressing is performed using a segmented pressing method to improve the stress distribution within the powder structure during the pressing process, increase the uniformity of the pressed green body, prevent stress locking within the green body from occurring during a single high-pressure dry pressing, and reduce the risk of delamination. In different embodiments, the mold filling depth can be 100mm-300mm.
[0022] Specifically, the pressurization method for dry pressing varies depending on the maximum depth of alumina particles filling the mold. In a preferred embodiment, when the maximum depth of alumina particles filling the mold is less than 30 mm, the pressure is first increased to a first pressure of 0.3 MPa-0.6 MPa, and held for at least 10 seconds; then, the pressure is increased to a second pressure of 8 MPa-12 MPa, and held for at least 30 seconds; finally, the pressure is increased to a third pressure of 25 MPa-35 MPa, and held for at least 30 seconds. The pressurization rate is controlled at 0.5 MPa / s-2 MPa / s. After holding at the third pressure, the pressure is released to atmospheric pressure at a release rate of 0.8 MPa / s-1.2 MPa / s.
[0023] When the maximum filling depth of alumina granules in the mold is 30mm-100mm, first apply pressure to a first pressure of 1MPa-1.7MPa, holding for at least 10s; then apply pressure to a second pressure of 17MPa-23MPa, holding for at least 40s; finally apply pressure to a third pressure of 35MPa-45MPa, holding for at least 30s. After holding at the third pressure, first release pressure at a rate of 0.4MPa / s-0.6MPa / s to 13MPa-17MPa and hold for at least 10s, then release pressure to atmospheric pressure at a rate of 0.8MPa / s-1.2MPa / s.
[0024] When the maximum filling depth of alumina particles in the mold exceeds 100mm, the pressure is first increased to a first pressure of 0.5MPa-1.7MPa, and held for at least 20s; then increased to a second pressure of 35MPa-45MPa, and held for at least 30s; finally, increased to a third pressure of 90MPa-110MPa, and held for at least 30s. After holding at the third pressure, the pressure is first released at a rate of 0.4MPa / s-0.6MPa / s to 50MPa-70MPa and held for at least 30s, then released to atmospheric pressure at a rate of 0.8MPa / s-1.2MPa / s. In a preferred embodiment, the resulting circular dry-pressed blank with a thickness exceeding 30mm is as follows: Figure 1 As shown, its structure is intact, and the surface is free of defects such as cracks and chipping. In a comparative example, a circular dry-pressed blank with a thickness exceeding 30 mm was obtained by one-time pressurization and direct depressurization, as shown in the figure. Figure 5 As shown, the dry-pressed billet exhibits obvious delamination, particularly with significant material loss in the edge region.
[0025] When the maximum filling depth of alumina granular raw material exceeds 30mm, segmented and slow pressure release can avoid stress imbalance caused by sudden release of internal compressive stress in the billet. During the pressure holding stage, the elastic aftereffect is fully released to prevent delamination caused by the elastic aftereffect of a thick billet.
[0026] The density of the dry-pressed preform obtained after dry pressing is not less than 30%, and in the preferred embodiment, it is not less than 40%.
[0027] Step c): The dry-pressed billet is subjected to cold isostatic pressing to obtain a cold isostatic pressed billet. The density of the cold isostatic pressed billet is not less than 50%, and in the preferred embodiment, not less than 55%. In the preferred embodiment, the specific process of cold isostatic pressing is as follows: pressurize to 0.5MPa-1.7MPa and hold for 0-30s, then pressurize to 25MPa-35MPa at a rate of 0.8MPa / s-1.2MPa / s and hold for 0-90s, then pressurize to 70MPa-90MPa at a rate of 1.7MPa / s-2.3MPa / s and hold for 0-120s; then depressurize to 35MPa-45MPa at a rate of 0.4MPa / s-0.6MPa / s and hold for 0-60s, and finally depressurize to atmospheric pressure at a rate of 0.8MPa / s-1.2MPa / s.
[0028] Cold isostatic pressing can eliminate the density and stress gradients caused by dry pressing, effectively improving the density of the billet. The density of the billet is measured; if it is less than 50%, the cold isostatically pressed billet is crushed into powder and re-dry-pressed.
[0029] Step d): The cold isostatically pressed green body with acceptable density is loaded into a muffle furnace and heated to 500℃-700℃ for 5-10 hours. In a preferred embodiment, the heating time is 24-48 hours. Then, it is heated to 1100℃-1300℃ and held for 2-5 hours. In a preferred embodiment, the heating time is 20-30 hours. After holding, it is first cooled to 500℃-700℃ over 20-30 hours, and then allowed to cool naturally to obtain the first sintered green body. Slow heating allows the organic matter mixed in the green body to fully vaporize, expels gas from the green body, and releases green stress, giving the first sintered green body a certain structural strength and preventing drastic shrinkage after cooling.
[0030] Step e): The first sintered billet is surface-processed to correct dimensional deviations and remove any minor surface defects, improving surface roughness and preventing defects from becoming crack initiations during subsequent processing. Subsequently, the first sintered billet is dried. In a preferred embodiment, the drying process is carried out at 90℃-110℃ for 12h-24h.
[0031] Step f): The first sintered blank is heated to 1100℃-1300℃ and held for 5-10 hours, then heated to 1500℃-1800℃ and held for 2-5 hours. After cooling, the finished alumina ceramic part is obtained. In a preferred embodiment, the heating time to 1100℃-1300℃ is controlled at 10-20 hours, and the heating time to 1500℃-1800℃ is 80-120 hours. During cooling, the temperature is first lowered to 500℃-700℃ over a period of 120-150 hours, and then naturally cooled to room temperature. By controlling the heating rate at a very low level, it is possible to ensure uniform temperature distribution within the large-volume blank, reduce temperature gradients in different areas, promote uniform grain growth, and eliminate internal stress. During the cooling process, by strictly controlling the cooling rate, it is ensured that the grains grow slowly and fully release grain boundary stress, preventing cracking caused by uneven thermal stress distribution during cooling.
[0032] In a preferred embodiment, the heating and cooling process in the above steps controls the temperature to change uniformly. This can be achieved by uniform heating and cooling or by uniform gradient heating and cooling, to avoid significant changes in the rate of temperature change during heating or cooling. Preferably, the fluctuation of the maximum rate of temperature change is controlled to be no more than 5% of the average rate of temperature change.
[0033] The large-volume alumina ceramic parts manufactured using the above method have uniform microstructure and properties, complete grain development, and no internal pores or cracks. The final product density can reach over 97%, enabling the sintering and manufacturing of alumina ceramic parts with a thickness exceeding 100 mm.
[0034] In a preferred embodiment, the manufacturing process of the alumina ceramic part is as follows: Hollow spherical alumina powder manufactured by spray granulation was used as raw material. Alumina powder with a particle size of 50μm-300μm was obtained by sieving with 50 mesh and 300 mesh sieves. Its flowability was measured to be 2.72s / 50g.
[0035] The raw material was filled using a 380mm × 380mm square mold with a filling depth of 117mm. During filling, the pressure was first maintained at 1MPa for 20s, then increased to 40MPa at a rate of 1MPa / s and held for 30s; next, the pressure was increased to 100MPa at a rate of 2MPa / s and held for 30s; after this holding period, the pressure was released to 60MPa at a rate of 0.5MPa / s and held for 30s; finally, the pressure was released to atmospheric pressure at a rate of 1MPa / s. The calculated density of the dry-pressed preform was approximately 34%.
[0036] The dry-pressed billet was subjected to cold isostatic pressing, with pressure increased to 1 MPa and held for 20 s, followed by increasing the pressure at a rate of 1 MPa / s to 30 MPa and holding for 30 s; then increasing the pressure at a rate of 2 MPa / s to 80 MPa and holding for 30 s; after holding the pressure, the pressure was released at a rate of 0.5 MPa / s to 40 MPa and held for 30 s; finally, the pressure was released at a rate of 1 MPa / s. The density of the billet after cold isostatic pressing was approximately 58%.
[0037] The cold isostatically pressed green body was heated from room temperature to 600°C over a 48-hour heating period and held at that temperature for 10 hours. It was then further heated to 1200°C over a 20-hour heating period and held at that temperature for 3 hours. Next, it was cooled from 1200°C to 600°C over a 20-hour cooling period, and finally allowed to cool naturally to room temperature to obtain the first sintered green body. The density of the first sintered green body was approximately 46%.
[0038] The surface of the first sintered blank is machined to the designed dimensions; then it is dried at 100°C for 12 hours.
[0039] The first sintered green body, after drying, was heated from room temperature to 1200℃ over a 16-hour heating period and held at that temperature for 8 hours. It was then further heated to 1800℃ over a 96-hour heating period and held at that temperature for 5 hours. After holding at that temperature, it was cooled to 600℃ over a 120-hour cooling period and finally allowed to cool naturally to room temperature to obtain the finished alumina ceramic part. Its density is 97%, the surface is pale yellow, and it is free of defects such as cracks or pores.
[0040] In another preferred embodiment, the manufacturing process of the alumina ceramic part is as follows: Hollow spherical alumina powder manufactured by spray granulation was used as raw material. Alumina powder with a particle size of 50μm-300μm was obtained by sieving with 50 mesh and 300 mesh sieves. Its flowability was measured to be 2.72s / 50g.
[0041] A square mold measuring 420mm × 300mm with a filling depth of 150mm was used for filling the raw material. One side of the mold had a rounded edge. During the filling process, the pressure was first maintained at 1.5MPa for 20s, then increased to 40MPa at a rate of 1MPa / s and held for 30s; next, the pressure was increased to 100MPa at a rate of 2MPa / s and held for 30s; after the pressure holding period, the pressure was released to 60MPa at a rate of 0.5MPa / s and held for 30s, and finally released to atmospheric pressure at a rate of 1MPa / s. The calculated density of the dry-pressed preform was approximately 37%.
[0042] The dry-pressed billet was subjected to cold isostatic pressing, with pressure increased to 1 MPa and held for 20 s, followed by increasing the pressure at a rate of 1 MPa / s to 30 MPa and holding for 30 s; then increasing the pressure at a rate of 2 MPa / s to 80 MPa and holding for 30 s; after holding the pressure, the pressure was released at a rate of 0.5 MPa / s to 40 MPa and held for 30 s; finally, the pressure was released at a rate of 1 MPa / s. The density of the billet after cold isostatic pressing was approximately 57%.
[0043] The cold isostatic pressed green body was heated from room temperature to 600°C over a 24-hour heating period and held at that temperature for 10 hours. Subsequently, it was further heated to 1200°C over a 30-hour heating period and held at that temperature for 5 hours. Next, it was cooled from 1200°C to 600°C over a 30-hour cooling period, and finally allowed to cool naturally to room temperature to obtain the first sintered green body. The density of the first sintered green body was approximately 46%. The first sintered green body is shown below. Figure 2 As shown, its surface is smooth and intact, without cracks, pores or other defects.
[0044] The first sintered blank is surface-machined to the designed dimensions; then dried at 100°C for 24 hours.
[0045] The dried first sintered green body was heated from room temperature to 1200℃ over a 20-hour heating period and held at that temperature for 10 hours; then heated further to 1800℃ over a 120-hour heating period and held at that temperature for 2 hours; after holding at that temperature, it was cooled to 600℃ over a 148-hour cooling period, and finally allowed to cool naturally to room temperature to obtain the finished alumina ceramic part, such as... Figure 3 As shown, its density is 97%, the surface is pale yellow, and there are no defects such as cracks or pores. The microstructure of this alumina ceramic part is as follows: Figure 4 As shown, its microstructure is uniform and dense, without defects such as pores or cracks.
[0046] The manufacturing method for large-volume alumina ceramic parts provided in the above embodiments can be used to prepare large alumina ceramic parts with a thickness exceeding 100 mm and a size exceeding 300 mm. The resulting finished product has a uniform and complete structure, without delamination or hidden cracks, and the deformation after sintering does not exceed 10%. This method can effectively eliminate the problems of uneven density distribution and numerous micro-defects existing in the manufacturing of alumina ceramic blanks using existing technologies, effectively reducing initial defects and improving the quality of the finished product. The alumina ceramic parts manufactured using this method have high dimensional accuracy and small deformation, and can meet high-precision assembly requirements without extensive subsequent machining. It is suitable for applications such as heat pipe micro-stacking reflector layers, which have extremely high requirements for dimensional accuracy and microstructure quality.
[0047] The purpose of the above embodiments is to provide a further detailed description of the present invention in conjunction with the accompanying drawings, so that those skilled in the art can understand the technical concept of the present invention. Within the scope of the present invention, optimization or equivalent substitution of the technical features involved, as well as combination of implementation methods in different embodiments without causing structural and principle conflicts, all fall within the protection scope of the present invention.
Claims
1. A method for manufacturing large-volume alumina ceramic parts, characterized in that, Includes the following steps: Step a): Provide alumina granular raw material; Step b): The alumina granular raw material is loaded into a mold for dry pressing. The dry pressing process involves sequentially applying pressure to the alumina granular raw material to a first pressure, a second pressure, and a third pressure, and holding the pressure at each pressure. Then, the pressure is released to atmospheric pressure to obtain a dry-pressed blank. The density of the dry-pressed blank is not less than 30%. Step c): The dry-pressed billet is subjected to cold isostatic pressing to obtain a cold isostatic pressed billet; the density of the cold isostatic pressed billet is not less than 50%. Step d): The cold isostatic pressed billet is heated to 500℃-700℃ and held for 5h-10h, then heated to 1100℃-1300℃ and held for 2h-5h to obtain the first sintered billet; Step e): Perform surface processing and drying on the first sintered blank; Step f): Heat the first sintered green body to 1100℃-1300℃ and hold for 5h-10h, then heat to 1500℃-1800℃ and hold for 2h-5h; after cooling, the finished alumina ceramic part is obtained.
2. The method for manufacturing large-volume alumina ceramic parts according to claim 1, characterized in that, The alumina granular raw material has a particle size of 50μm-300μm and a flowability of 2s / 50g-4s / 50g.
3. The method for manufacturing large-volume alumina ceramic parts according to claim 1 or 2, characterized in that, The alumina granules are hollow spherical particles, and the alumina granules are manufactured using a spray granulation process.
4. The method for manufacturing large-volume alumina ceramic parts according to claim 1, characterized in that, In step b): When the maximum filling depth of the alumina granular raw material in the mold is less than 30mm, the first pressure is 0.3MPa-0.6MPa, and the holding time is not less than 10s; the second pressure is 8MPa-12MPa, and the holding time is not less than 30s; the third pressure is 25MPa-35MPa, and the holding time is not less than 30s. When the maximum filling depth of the alumina granular raw material in the mold is 30mm-100mm, the first pressure is 1MPa-1.7MPa, and the holding time is not less than 10s; the second pressure is 17MPa-23MPa, and the holding time is not less than 40s; the third pressure is 35MPa-45MPa, and the holding time is not less than 30s. When the maximum filling depth of the alumina granular raw material in the mold is greater than 100mm, the first pressure is 0.5MPa-1.7MPa, and the holding time is not less than 20s; the second pressure is 35MPa-45MPa, and the holding time is not less than 30s; the third pressure is 90MPa-110MPa, and the holding time is not less than 30s. The pressurization rate is 0.5 MPa / s to 2 MPa / s.
5. The method for manufacturing large-volume alumina ceramic parts according to claim 1 or 4, characterized in that, In step b), after pressurizing to the third pressure and maintaining the pressure, When the maximum filling depth of the alumina particles in the mold is less than 30 mm, the pressure is released to atmospheric pressure at a rate of 0.8 MPa / s-1.2 MPa / s. When the maximum filling depth of the alumina granular raw material in the mold is 30mm-100mm, the pressure is first released to 13MPa-17MPa at a rate of 0.4MPa / s-0.6MPa / s and held for at least 10s, and then released to atmospheric pressure at a rate of 0.8MPa / s-1.2MPa / s. When the maximum filling depth of the alumina particles in the mold is greater than 100 mm, the pressure is first released to 50 MPa-70 MPa at a rate of 0.4 MPa / s-0.6 MPa / s and held for at least 30 seconds, and then released to atmospheric pressure at a rate of 0.8 MPa / s-1.2 MPa / s.
6. The method for manufacturing large-volume alumina ceramic parts according to claim 1, characterized in that, In step c), the specific process of the cold isostatic pressing is as follows: pressurize to 0.5MPa-1.7MPa and hold for 0-30s, then pressurize to 25MPa-35MPa at a rate of 0.8MPa / s-1.2MPa / s and hold for 0-90s, then pressurize to 70MPa-90MPa at a rate of 1.7MPa / s-2.3MPa / s and hold for 0-120s; then depressurize to 35MPa-45MPa at a rate of 0.4MPa / s-0.6MPa / s and hold for 0-60s, and finally depressurize to atmospheric pressure at a rate of 0.8MPa / s-1.2MPa / s.
7. The method for manufacturing large-volume alumina ceramic parts according to claim 1, characterized in that, In step d), the heating time for heating the cold isostatic pressing blank to 500℃-700℃ is 24h-48h, and the heating time for heating to 1100℃-1300℃ is 20h-30h; during cooling, the blank is first cooled to 500℃-700℃ over a period of 20h-30h, and then naturally cooled to room temperature.
8. The method for manufacturing large-volume alumina ceramic parts according to claim 1, characterized in that, In step e), the drying temperature is 80℃-120℃ and the drying time is 12h-24h.
9. The method for manufacturing large-volume alumina ceramic parts according to claim 1, characterized in that, In step f), the heating time to 1100℃-1300℃ is 10h-20h, and the heating time to 1500℃-1800℃ is 80h-120h; when cooling down, the temperature is first lowered to 500℃-700℃ in 120h-150h, and then naturally cooled to room temperature.
10. A large-volume alumina ceramic part, characterized in that, It is manufactured using the manufacturing method for large-volume alumina ceramic parts as described in any one of claims 1 to 9.
11. The large-volume alumina ceramic part according to claim 10, characterized in that, The density of the large-volume alumina ceramic parts is not less than 95%.